2019
DOI: 10.1111/bjd.18216
|View full text |Cite
|
Sign up to set email alerts
|

Recessive mosaicism in ABCA12 causes blaschkoid congenital ichthyosiform erythroderma

Abstract: Summary We report the unique case of a 3‐year‐old girl who presented with linear erythematosquamous lesions following the lines of Blaschko, suggestive of genetic mosaicism in the skin. Single‐candidate gene analyses were performed on DNA from blood, excluding Conradi–Hünermann–Happle syndrome, erythrokeratodermia variabilis and a mosaic presentation of pityriasis rubra pilaris. With whole‐exome sequencing (WES) on DNA from the patient's blood, a heterozygous missense mutation in exon 25 of the ABCA12 gene was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…As clearly observed, no pathogenic variations in SPINK5 gene, neither in genes involved in erythrokeratoderma variabilis (EKV) were found in ILC patients (data not shown), confirming then different etiologies. Recently, Leersum et al [ 39 ] also reported a novel clinical phenotype of ichthyosis in a 3-year-old girl presenting a linear erythematosquamous lesions following the lines of Blaschko caused by ABCA12 mosaicism. This particular form of ichthyosis was explained by the combination of a germline mutation and an acquired postzygotic mutation in this gene.…”
Section: Discussionmentioning
confidence: 99%
“…As clearly observed, no pathogenic variations in SPINK5 gene, neither in genes involved in erythrokeratoderma variabilis (EKV) were found in ILC patients (data not shown), confirming then different etiologies. Recently, Leersum et al [ 39 ] also reported a novel clinical phenotype of ichthyosis in a 3-year-old girl presenting a linear erythematosquamous lesions following the lines of Blaschko caused by ABCA12 mosaicism. This particular form of ichthyosis was explained by the combination of a germline mutation and an acquired postzygotic mutation in this gene.…”
Section: Discussionmentioning
confidence: 99%
“…10 As we were unable to analyze the DNA samples from the epidermis in this study, we are unable to completely exclude the possibility of revertant mosaicism in keratinocytes within unaffected areas in the present cases. van Leersum et al 4 reported a patient with blaschkoid CIE due to biallelic pathogenic variants, one being an inherited germline missense variant and the other being a postzygotic frameshift variant in ABCA12. However, the hyperkeratotic areas in the present cases did not follow the Blaschko lines.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, pathogenic variants in ABCA12 are known to cause a localized nevoid form of CIE due to recessive mosaicism. 4 ABCA12 belongs to the large superfamily of adenosine triphosphate-binding cassette (ABC) transporter genes. ABC transporters bind ATP for the transport of various molecules across the limiting membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, while there is a large number of autosomal recessive genodermatoses and there are millions of carriers of the gene variants in the associated genes, segmental type 1 mosaicism for such recessive genodermatoses is only rarely reported. One of the few examples is a case of blaschkoid congenital ichthyosiform erythroderma due to somatic mosaicism for a second ABCA12 variant [ 21 ]. While this has not been thoroughly investigated, this lack of observations may reflect that, for many disorders, cells lacking the protein encoded by the gene involved have a developmental disadvantage.…”
Section: Forward Mosaicism In Genodermatosesmentioning
confidence: 99%